Business networks : strategy and structure - Todeva, Emanuela, 1961- (Routledge, 2006)
Introduction -- Definition of the term "network" -- Network characteristics -- The nature of network members and their behaviour -- Relationship in business networks -- Network structures -- Network communications and linkages between members -- Management of business networks -- International business networks -- Business networks in China -- Business networks in transition economies - case studies from Central and Eastern Europe
Keywords: strategické aliance; podnikatelské sítě; kooperace podniků